2013
DOI: 10.2169/internalmedicine.52.0311
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation of the <i>GAA</i> Gene in a Patient with Adult-onset Pompe Disease Lacking a Disease-specific Pathology

Abstract: We herein report a novel compound heterozygous mutation of the acid α-glucosidase (GAA) gene in a 23-year-old man with adult-onset Pompe disease. The patient was admitted for respiratory failure and a highly elevated serum level of creatine kinase (CK). His muscle pathology did not show typical vacuolated fibers; however, globular inclusion bodies with acid phosphatase (ACP) activity was observed. A molecular genetic analysis of the GAA gene revealed a novel compound heterozygous mutation, c.1544 T>A (M515K), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Interestingly, lipofuscin inclusions are often seen in otherwise normal looking fibers. It was suggested that these acid phosphatase-positive/periodic acid Schiff (PAS)-negative inclusions may be a hallmark of the disease and a diagnostic marker, particularly in adult form, which every so often represent the diagnostic challenge (Tsuburaya et al, 2012; Fujimoto et al, 2013). …”
Section: Pathogenesismentioning
confidence: 99%
“…Interestingly, lipofuscin inclusions are often seen in otherwise normal looking fibers. It was suggested that these acid phosphatase-positive/periodic acid Schiff (PAS)-negative inclusions may be a hallmark of the disease and a diagnostic marker, particularly in adult form, which every so often represent the diagnostic challenge (Tsuburaya et al, 2012; Fujimoto et al, 2013). …”
Section: Pathogenesismentioning
confidence: 99%
“…The GAA gene on chromosome 17q25.2–25.3 is a long gene with 20 exons encoding a protein with 952 amino acids. More than 450 different mutations, including missense, nonsense, small or large deletions/insertions, and frameshift mutations, have been reported along the length of this gene . There is a good correlation between the type of mutation, the degree of residual enzyme activity, and the severity of clinical presentations …”
mentioning
confidence: 99%
“…GAA variants classified as variants of uncertain significance (VUS) because of insufficient pathogenic evidence (c.1669A>T (p.Ile557Phe) and c.2132C>G (p.Thr711Arg) reported by Kim EH et al [ 27 ]) or GAA variants described in an incorrect nomenclature were excluded in this study. A total of 17 studies on Japanese patients with Pompe disease were reviewed [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], and 29 different GAA PLPVs (total of 130 PLPV alleles) were reported in 76 Japanese patients with Pompe disease. Of the GAA variants reported in 17 Japanese studies, 11 were classified as VUS and one was classified as benign, which were excluded from this analysis.…”
Section: Resultsmentioning
confidence: 99%